Increasing 10th grade students’ mathematical representation through mind mapping strategy - P K Sari; S Suhendra; A Jupri (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Mathematical representation is one of the important abilities mastered by students, in an attempt to find a solution of a problem, both math problems, as well as daily problems. One way to increase this ability is through mind mapping strategy. Mind mapping strategy involves students actively in mapping information through effective note-taking techniques. The mind map process shows a picture of interconnectedness, and a clear relationship between concepts. In expressing an idea, students can recall information associated with the learned knowledge by projecting the idea into a map or graphic technique. In addition, mind mapping activities can enhance students creativity through freedom of imagination, so learning becomes more interesting. The main problem in this research is whether mind mapping strategy can increase students mathematical representation. This research is a quasi-experiment with nonequivalent control group designs. This research involves 63 tenth grade students in Muara Bungo, Jambi. The result of this research is a significant improvement to students mathematical representation through mind mapping strategy.